Determinants of subjective job insecurity in 5 European countries - Muñoz de Bustillo, Rafael; de Pedraza, Pablo (Amsterdam, 2007)
"The present study searches for subjective job insecurity predictors in five European countries (Spain, Belgium, Finland, The Netherlands and Germany). The results find conclusions regarding demographic variables, such as age, gender, educational level; type of contract; family life variables, such as having an employed partner or children living at home; firm characteristics, such as its size or whether it is increasing or decreasing its labour force; and economic context such as living in a region characterized by favourable labour market conditions."